Chemical composition and antioxidant properties of five edible Hymenomycetes mushrooms. (12th August 2014) - Zhang, Ning; Chen, Haixia; Zhang, Yu; Xing, Lisha; Li, Shuqin; Wang, Xiuming; Sun, Zhen
Summary Ethanol extracts (LEE: ethanol extract from Lentinus edodes; TEE: ethanol extract from Tremella fuciformis; AEE: ethanol extract from Auricularia polytricha; GEE: ethanol extract from Ganoderma lucidum; IEE: ethanol extract from Inonotus obliquus) and water extracts (LWE: water extract from Lentinus edodes; TWE: water extract from Tremella fuciformis; AWE: water extract from Auricularia polytricha; GWE: water extract from Ganoderma lucidum; IWE: water extract from Inonotus obliquus) were obtained from five mushrooms. The contents of their main active constituents were analysed, and the antioxidant properties were studied by three in vitro assay systems. It was found that IEE had the highest phenolic content (55.94 mg g−1), flavonoid content (67.33 mg g−1) and the contents of five individual phenolic compounds (total amount was 4538.36 μg g−1). The highest content of neutral sugar was found in TWE (668.10 mg g−1), uronic acid in AWE (134.42 mg g−1), and the protein content was the highest in IWE (523.79 mg g−1). The antioxidant order was Inonotus obliquus > Ganoderma lucidum > Lentinus edodes > Tremella fuciformis > Auricularia auricula. IEE showed the highest antioxidant activities, and it might be used as a new candidate antioxidant.